Ships with angels, Port House - Ghosh, Ayan (2023)
The maritime nature of the Port House (Old Bombay Port Trust Building) is highlighted by the presence of medieval ships projecting from the wall on the upper level of the porch. Two ships jut out of the wall, only half of their length visible. Both feature a figurehead of a winged angel attached to the bow (the forward-most part of the ship).